Enzymes from Cereal and Fusarium Metabolism Involved in the Malting Process – A Review. (10th January 2022) - Geißinger, Cajetan; Gastl, Martina; Becker, Thomas
Abstract: The enzymatic properties of brewing malts are an important and sometimes limiting factor in malt and beer production. In order to observe malt quality, multiple analytical tests were developed for determining the various enzymatic activities of brewing-related enzymes in brewing cereals and their corresponding malts. When using the prevailing detection methods, little or no attention has been paid to the microbiological status of the processed cereals. Infection of cereals with Fusarium spp. can lead to a deterioration in cereal and malt quality. This weakening in quality during cereal processing is mostly attributed to enzymatic degradations. The enzymes involved can be cereal-borne as well as fungal, in which case enzymes up- or down-regulation can be often ascribed to pathogenesis-related protein secretion or can be a result of host-pathogen interactions. Accordingly, when determining the enzyme activity of infested grain, an increase in enzyme activity is usually detected.